1977
DOI: 10.1161/01.cir.55.4.569
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of sinoatrial conduction in patients with coronary artery disease.

Abstract: Electrophysiologic studies were performed in 32 patients with angiographically documented coronary artery disease (CAD). Group I was composed of ten patients (31%) with severe stenosis (greater than or equal to 75%) proximal to the origin of the sinus node artery (SNA); group II was composed of five patients (16%) with moderate (50--75%) proximal stenosis; and group III was composed of 17 patients (53%) with insignificant (0--50%) proximal stenosis. The mean sinoatrial conduction time (SACT) for group I was 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In a previous report, Jordan, et al found significant sinoatrial conduction time (SACT) prolongation in patients with sinus nodal artery insufficiency and suggested a pathogenetic role of CAD in the development of sinus nodal dysfunction. 9) However, Shaw, et al reported only 4 of 25 patients with chronic sinoatrial disorder had angiographic evidence of more then Vol 42 No 4 75% stenosis obstructing the sinus nodal artery.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, Jordan, et al found significant sinoatrial conduction time (SACT) prolongation in patients with sinus nodal artery insufficiency and suggested a pathogenetic role of CAD in the development of sinus nodal dysfunction. 9) However, Shaw, et al reported only 4 of 25 patients with chronic sinoatrial disorder had angiographic evidence of more then Vol 42 No 4 75% stenosis obstructing the sinus nodal artery.…”
Section: Discussionmentioning
confidence: 99%
“…Results of Alboni et al showed for the first time in the clinical setting a role for the SNA disease in the pathogenesis of SSS in a selected group of their patients [2]. In two previous studies, the electrophysiologic measures of sinus node were correlated with the severity of SNA disease, but in subjects with normal sinus rate and only in the basal state [4,5]. Engel et al failed to demonstrate a correlation between the prolongation of corrected sinus node recovery time and the presence or the extent of atherosclerotic lesions proximal to the origin of the SNA [4].…”
Section: Discussionmentioning
confidence: 99%
“…In about 30% of their cases, the SACT by both methods coincided well, The significance of SACT is still controversial. Some investigators reported that the estimation of SACT is useful to differentiate patients with sinus node dysfunction from patients with normal sinus node function.10),14), 15) Other investigators concluded from their results that programmed atrial stimulation is not of great clinical value.12),16),17) However, most authors still believe, although the Strauss method has many problems and the limitations, that this method is currently the best available for characterization of sinoatrial conduction. And now it is potentially possible to differentiate the abnormal sinus node automaticity and impaired impulse conduction through peri-nodal fibers despite the fact that the differentiation is sometimes difficult because these abnormalities are occasionally combined.…”
Section: Discussionmentioning
confidence: 99%